STORING THE GASOLINE THE CONSTRUCTION OF INTRA-ETHNIC AND INTER-ETHNIC CIRMUSTANCES Building Peace and Constructing Conflict in Civil Society - Andini, Batari Oja (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2017)
This paper is aimed to find the cause of conflict in civil society by exploring the concept of intra-ethnic and inter-ethnic society offered by Ashutosh Varshney. According to Varshney, intra-ethnic engagement would lead the society to ethnic violence. On the contrary, inter-ethnic engagement would lead society to ethnic peace. This paper will show that inter-ethnic and intra-ethnic engagementsare impermanent circumstances, which are constructed by society. The inter-ethnic and intra-ethnic circumstances could be conducted by performing or not performing the symbols of each ethnic group. The example mentioned in this paper is the interaction between two religious-ethnic groups, namely; Buddhist-Tionghoa and Christian-Torajan. The data of the example were gained by doing qualitative fieldwork, particularly participatory observation.